The attention-intention-effort pathway in the development of psychophysiologic insomnia: a theoretical review. - Espie, C; Broomfield, N; MacMahon, K; Macphee, L; Taylor, L (2006)
Psychophysiologic insomnia (PI) is the most common form of persistent primary insomnia. Its 'behavioral phenotype', comprising elements such as conditioned arousal, sleep-incompatible behavior and sleep preoccupation, has not changed markedly across several generations of diagnostic nosology. Moreover, a substantial outcome literature demonstrates that PI can be treated effectively using a range of psychological interventions. It seems evident that behavioral and cognitive factors play a part. What is less clear is exactly how PI develops and what are its crucial maintaining factors. This paper proposes an explanatory model, that we call the attention-intention-effort pathway. The argument is that sleep normalcy is a relatively automatic process. Consequently, it is vulnerable, and may be inhibited, by focused attention and by direct attempts to control its expression. Drawing upon parallels in the literature on adult psychopathology, and upon recent clinical and experimental studies on insomnia, the evidence for this pathway is considered and a research agenda is outlined. In particular, computerized tests of cognitive bias are seen as offering an objective means of appraising mental processes in insomnia. These may be applied concurrently with somatic measurements in future studies to better understand this common psycho-physiologic condition.